Nilai-Nilai Pendidikan Karakter dalam Novel Teruslah Bodoh Jangan Pintar Karya Tere Liye dan Ladang Perminus Karya Ramadhan K.H: Kajian Intertekstual - Harlita; Syofiani Syofiani; Husnul Fikri (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Character education is a form of human activity in which there is an educational action, intended for the next generation. The purpose of character education is to shape the individual continuously and train one's abilities in order to move towards a better life. As for this research, there is knowing the theme, characterization, plot and setting in the novel Teruslah Bodoh Jangan Pintar by Tere Liye and Ladang Perminus by Ramadhan K.H., knowing the value of educational character contained in the novel Teruslah Bodoh Jangan Pintar by Tere Liye and the novel Ladang Perminus by Ramadhan K.H., and the similarities and differences in the value of character education in the novel Teruslah Bodoh Jangan Pintar by Tere Liye and the novel Ladang Perminus by Ramadhan K.H. The type of research used is qualitative research that produces descriptive data. The research method used is a descriptive method. the relationship between the two novels. Both novels have the same theme about the problem of character education values, The plots of the two novels are different, Teruslah Bodoh Jangan Pintar has a forward-backward plot while Ladang Perminus has a forward plot. The background of the two novels is somewhat different. The novel "Keep Being Stupid, Don't Be Smart" is set in a former mining site, a rural area, and a courtroom, while the novel "Ladang Perminus" is set at the Perminus company and also in Singapore. Despite their different settings, the two novels complement each other in providing an understanding of the character values ​​of education: love of country, environmental awareness, and social awareness.